Acesso aberto e visibilidade à produção intelectual da UFMG: organização e difusão dos acervos da Escola de Arquitetura - Izabel Antonina de Araújo (2017)
The study aimed to implement an open-access policy for the Federal University of Minas Gerais (UFMG). To that end, a case study was developed at the School of Architecture. The open-access policy here elaborated aims at promoting institutional visibility and giving back to the society the knowledge generated in the Institution. Considering the size of the University and the diversity of its scientific production, the study began based on the School of Architecture’s experience – one of the Institution’s 23 academic units. The criteria for selection included the specificity of the bibliographic production and the representativeness of the School of Architecture for Minas Gerais and for Brazil. This is a descriptive research that uses the case study as method; resources used included bibliographic research, documentary research, interviews, questionnaires and participant observation. By using these instruments, it was possible to investigate the main concepts and information about the state of the art for open access to information in the national and international contexts. Additionally, the intellectual production by professors in the School of Architecture was described qualitatively. Some topics of analysis were the views of professors and managers on the benefits provided by an institutional repository in their professional practices, the information needs of the school regarding organization and dissemination of academic production, the process of internationalization undergone by the school's production as well as the motivation to collaborate with the production input in the repository and the way in which this policy should be inserted in the University. This action sought to identify elements that support the planning of information organization in a single repository with open access to information, which allows greater visibility for scientific and cultural productions by the School of Architecture at UFMG. The results of this research guided the decisions and guidelines for the implementation of the UFMG Institutional Repository and the construction of an information policy model.